Investigating the theory of planned behaviour's application to binge drinking among university students. (January 2013) - Ross, Anna; Jackson, Mervyn
<x xml:space="preserve">Abstract</x> The theory of planned behaviour (TPB) has been found to predict many health-related behaviours. The aim of this study was to further investigate the factors that predict binge drinking in university students using the TPB, and to further investigate social facilitation and self-efficacy in relation to binge drinking. One hundred and sixty-one university students completed a questionnaire (time 1), measuring attitude, subjective norms, perceived behavioural control (PBC) and binge-drinking intentions, and 2 weeks later (time 2) 142 participants reported their binge-drinking behaviour. Ninety-one participants completed both questionnaires. Multiple regression analyses found partial support for the application of the TPB to binge drinking among university students accounting for 50% of variance in intentions to binge drink and 73% of variance in predicting future binge-drinking behaviour. However, PBC was found to be a non-significant predictor, thus supporting the simpler model of behaviour which excludes this control variable, the theory of reasoned action. Self-efficacy and social facilitation were also significant predictors of binge drinking. These findings indicate that to reduce binge drinking in university students, interventions targeting attitude change, perception of social norms and social facilitation would be most effective. Future research should explore the role of PBC in the TPB to determine its relevance in binge drinking.